ФОРМУВАННЯ ЕСТЕТИЧНОГО СПРИЙНЯТТЯ СТАРШОКЛАСНИКІВ ЗАСОБАМИ СИНТЕЗУ МИСТЕЦТВ (Педагогіка вищої та середньої школи, 2009)
In the article the essence of concept "aesthetic perception" is defined, ways of information at pupils at lessons of art culture are considered, the modern approach in carrying out of lessons of art culture with use of synthesis of arts it offered.